Complicated appendicitis: Analysis of risk factors in children - Mahavir Singh; Yoginder Singh Kadian; Kamal Nain Rattan; Babita Jangra (Wolters Kluwer Medknow Publications, 2014)
Background: Acute appendicitis (AA) is the most common surgical emergency in childhood. The risk of rupture is negligible within the first 24 h, climbing to 6% after 36 h from the onset of symptoms. Because of difficulty in accurate diagnosis of AA a significant number of children still are being managed when it is already perforated. There is always a need to make an early diagnosis of AA and to find out the risk factors associated with development of complication in this condition. Patients and Methods: A total of 102 patients with a clinical diagnosis of AA were admitted during the study period. On admission, a good clinical history and proper physical examination was performed. All the eligible patients who finally diagnosed clinically as having AA were planned for emergency open appendectomy. The removed appendix was sent for histopathological examination in all the study subjects. Results: Out of 102 cases, 93 cases were histopathologically appendicitis, rest nine cases showed no evidence of inflammation so the rate of negative appendectomy was around 9%. On histopathology normal appendix was found in nine patients (8.9%), AA in 71 patients (69.6%), complicated appendicitis (CA) which includes perforated and gangrenous appendicitis was present in 22 patients (21.5%). Perforations were more common in patients who were younger than 5 years. >60% patients presented with CA when the duration of pain was >72 h. Presence of appendicolith increased the probability of CA.